SCHOOL CLOSURES AND CHILDREN’S EDUCATIONAL PROBLEMS DURING PANDEMIC IN AZAD JAMMU AND KASHMIR (The Research of Medical Science Review, 2025)
The COVID-19 pandemic significantly disrupted school education in unprecedented ways. This study aims to examine the challenges faced by children due to school closures during the pandemic. The primary objective was to identify the factors that negatively impacted the educational performance of schoolchildren. The study was conducted in two public schools in Mirpur, Azad Jammu and Kashmir (AJK), using a quantitative research design with a cross- sectional approach. Data was collected through a questionnaire with a sample of 405 students, selected using a convenience sampling technique. Our findings revealed a range of issues affecting students' performance, with regression analysis identifying key predictors of poor educational outcomes. These included a lack of technology, inadequate skills, limited internet access, issues with marking and grading, and increased stress. Consequently, students' academic performance was severely impacted. Our findings challenge the views of Conole (2007), Hannon (2008), Reid (2012), and Dahlberg (2004), who did not account for the extent of educational disruption observed. It is strongly recommended that the Ministry of Education (MoE) develop and implement preparedness programs to better address such crises in the future.